(untitled) (Progressive Agriculture, 2013)
An experiment was carried out to know the carnivorous feeding nature of piranha (Pygocentrus nattereri) under laboratory condition for a period of 36 days. One-month old nine fish were stocked in nine separate glass aquaria having three feeding treatments each with three replications. Fish were fed with nursery feed (Sabinco feed) in treatment 1 (T1); 50% live + 50% dead small prawns (Macrobrachium rosenbergii) and small fishes (Esomus danricus and Amblypharyngodon mola) in treatment 2 (T2); and 100% live small prawn and fishes in treatment 3 (T3) twice a day at the rate of 10% body weight. The average weight gain was significantly (P<0.05) higher in T2 (21.02 ± 0.72) than in T1 (-1.824 ± 0.35) and T3 (15.36 ± 4.96). The SGR (% day-1) recorded was significantly (P<0.05) higher in T2 (12.04 ± 0.01) than T3 (11.77 ± 0.09). No unused feed was found in T2 and T3 but some unused feed was found in T1. The stomach length, gut length and the RLG values of piranha were significantly (P<0.05) higher than that of taki, Channa punctatus but not of boal, Wallago attu. The presence of razor sharp teeth in both jaws and 30-32 pyloric caeca with 1.84 RLG value are attributed to the piranha as carnivore. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16764 Progress. Agric. 21(1 & 2): 151 - 158, 2010